Angle grinder injuries in orthopedics: A case series and review of the literature. (April 2021) - Curran, Michael G.; Clesham, Kevin; Irwin, Shane; Hughes, Andrew; Kennedy, Muiris
Abstract: Angle grinders are amongst the most dangerous tools used in industry and agriculture. Over 5000 documented injuries are related to their use each year which are commonly triggered by a shattering of the abrasive wheel. These injuries are often accompanied by suboptimal health and safety standards. The authors of this paper present three separate cases of accidental injuries presenting to our institution over a short time period. The authors main aim is to raise awareness surrounding the associated dangers of using such tools. A brief economic analysis also illustrates the significant costs involved in treating such preventable injuries.